Wetlands integrating multidisciplinary concepts - LePage, Ben A.; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
The science of wetlands and our understanding of these complex ecosystems have improved considerably. The emergence of multidisciplinary strategies is providing new opportunities and innovative approaches to address issues such as climate change and coastal protection. This book, with contributions from 19 specialists from academia, government, and industry, provides a trans-disciplinary approach to the understanding wetlands science, drawing together a wide range of expertise. Topics covered include the physical aspects that shape different wetlands around the world, as well as wetlands ecology, regulation, policy, and related social and economic issues. Featuring contributions from some of the world?s leading wetlands researchers and practitioners, this book provides an invaluable resource for undergraduate and post-graduate training in all aspects of wetlands management, conservation, and construction. It is also a useful auxiliary text for researchers working across disciplines in fields such as wetlands science, law, landscape architecture, environmental engineering, conservation ecology, and related disciplines.
1. Ben A. LePage - Wetlands: A multi-disciplinary perspective -- 2. Marjorie L. Zeff - The necessity for multi-disciplinary approaches to wetland design and adaptive management: the case of wetland channels -- 3. Andrew de Wet, Christopher J. Williams, Jaime Tomlinson and Erin Carlson Loy - Stream and Sediment Dynamics in Response to Holocene Landscape Changes in Lancaster County, Pennsylvania -- 4. Christopher J. Williams - A paleoecological perspective on wetland restoration -- 5. Mark M. Brinson - Classification of wetlands -- 6. J. Andrew Nyman - Ecological function of wetlands -- 7. Beth Middleton- Multidisciplinary approaches to climate change ecology -- 8. Andy Cole and Mary Kentula - Monitoring and assessment, what to measure and why -- 9. Rachel Kaplan - Acknowledging and benefiting from multiple perspectives -- 10. Morgan Robertson and Palmer Hough - Wetlands regulation: the case of mitigation under Section 404 of the clean water act -- 11. Royal Gardner and Nick Davidson - The ramsar convention -- 12. Robert J. McInnes - Managing Wetlands for multifunctional benefits -- 13. Nancy Minich - The role of landscape architects and wetlands -- 14. Lanshing Hwang and Ben A. LePage - Floating islands: an alternative to urban wetlands.
Electronic reproduction.
Keywords: Wetlands; Wetland ecology; Electronic books